A Study of Innovation Management at Braskem - Vanessa Theis (Desenvolvimento em Questão, 2016)
In the current economic climate, companies must seek new ways to manage innovation, which hasrecently become a key method of differentiation in competitive markets. The general goal of this ar-ticle was to study the process of innovation management in a petrochemical company. A case studyperformed at Braskem showed that the ability to manage and use knowledge is the major drive oftechnological innovation. Main contribution of the study, it is evident the use of methods aimed atencouraging internal innovation, as suggestions of employees and their selection using establishedscientific methods.